2009
DOI: 10.1145/1670564.1670582
|View full text |Cite
|
Sign up to set email alerts
|

The impact of MeSH (Medical Subject Headings) terms on information seeking effectiveness

Abstract: To what extent do MeSH (Medical Subject Headings) terms improve search effectiveness of different kinds of users? We observed four different kinds of searchers using an experimental information retrieval (IR) system: (1) search novices; (2) domain experts; (3) search experts and (4) medical librarians. The information needs were a subset of the relatively difficult topics originally created for the Text REtrieval Conference (TREC). By experimental design, we used 20 search topics in an IR user experiment to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…Liu reported, "experimental results strongly suggest that searchers with substantial domain knowledge can benefit from the use of MeSH terms in terms of the precision measure, even though their perception of the usefulness of MeSH terms did not agree with search performance." 45 Users' Difficulty with Subject Searching With so much evidence that scholars need more than keyword searching, why are some authors recommending that controlled vocabulary be abandoned? Several researchers have pointed out that many patrons cannot do subject searching successfully.…”
Section: Controlled Vocabulary Is Needed For Scholarly Researchmentioning
confidence: 99%
“…Liu reported, "experimental results strongly suggest that searchers with substantial domain knowledge can benefit from the use of MeSH terms in terms of the precision measure, even though their perception of the usefulness of MeSH terms did not agree with search performance." 45 Users' Difficulty with Subject Searching With so much evidence that scholars need more than keyword searching, why are some authors recommending that controlled vocabulary be abandoned? Several researchers have pointed out that many patrons cannot do subject searching successfully.…”
Section: Controlled Vocabulary Is Needed For Scholarly Researchmentioning
confidence: 99%
“…Finally, many scientists do not know how to use MEDLINE/PubMed to its full extent, especially when applying the MeSH terms (13). Liu demonstrated that MeSH terms differ in usefulness according to the user’s level of expertise (16). This means that the lack of familiarity with a specific topic and its MeSH term may lead to the loss of crucial information, even when using separate terms for each country, and could lead our brightening stars of LAC to fade away in the archive.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the overall clarity scores of the users, including those of advanced searchers, were very low. Liu (2009, p. 73) reports a similar result, that the TREC information retrieval systems generally performed much better than human searchers, including domain experts and search experts, at least on hard biomedical searches.…”
Section: Queriesmentioning
confidence: 99%